Interactions between visual and motor areas during the recognition of plausible actions as revealed by magnetoencephalography - Pavlidou, Anastasia (Hum Brain Mapp, 2012)
Several studies have shown activation of the mirror neuron system (MNS), comprising the temporal, posterior parietal, and sensorimotor areas when observing plausible actions, but far less is known on how these cortical areas interact during the recognition of a plausible action. Here, we recorded neural activity with magnetoencephalography while subjects viewed point‐light displays of biologically plausible and scrambled versions of actions. We were interested in modulations of oscillatory activity and, specifically, in coupling of oscillatory activity between visual and motor areas. Both plausible and scrambled actions elicited modulations of θ (5–7 Hz), α (7–13 Hz), β (13–35 Hz), and γ (55–100 Hz) power within visual and motor areas. When comparing between the two actions, we observed sequential and spatially distinct increases of γ (∼65 Hz), β (∼25 Hz), and α (∼11 Hz) power between 0.5 and 1.3 s in parieto‐occipital, sensorimotor, and left temporal areas. In addition, significant clusters of γ (∼65 Hz) and α/β (∼15 Hz) power decrease were observed in right temporal and parieto‐occipital areas between 1.3 and 2.0 s. We found β‐power in sensorimotor areas to be positively correlated on a trial‐by‐trial basis with parieto‐occipital γ and left temporal α‐power for the plausible but not for the scrambled condition. These results provide new insights in the neuronal oscillatory activity of the areas involved in the recognition of plausible action movements and their interaction. The power correlations between specific areas underscore the importance of interactions between visual and motor areas of the MNS during the recognition of a plausible action. Hum Brain Mapp 35:581–592, 2014. © 2012 Wiley‐Periodicals, Inc.